Predictive Factors of Early Recurrence in Patients with Distal Cholangiocarcinoma after Pancreaticoduodenectomy - Yasuhiro Ito; Yuta Abe; Tomohisa Egawa; Minoru Kitago; Osamu Itano; Yuko Kitagawa (Gastroenterology Research and Practice)
Aim. To determine the factors associated with early recurrence in patients with distal cholangiocarcinoma after pancreaticoduodenectomy (PD). Patients and Methods. Sixty-one patients with distal cholangiocarcinoma were enrolled. The clinical data and histopathological findings were collected retrospectively. Results. Patients were divided into two groups as follows: 16 patients (26%) with early recurrence and 45 patients (74%) with late recurrence or no recurrence. In a univariate analysis, lymph node metastases (P=0.0016), lymphatic invasion (P<0.0001), pancreatic invasion (P=0.0006), and perineural invasion (P=0.0004) were significantly different between the two groups. In a multivariate analysis, a higher incidence of lymphatic invasion was the only independent risk factor for early recurrence (odds ratio: 5.772, 95% confidence interval: 1.123–29.682, P=0.036). Moreover, the disease-free survival and overall survival of patients with a higher incidence of lymphatic invasion were significantly worse compared with those of patients with a lower incidence of lymphatic invasion (P<0.001). Conclusions. Our study showed that a higher incidence of lymphatic invasion was a significant predictor of early recurrence in patients with distal cholangiocarcinoma. Therefore, lymphatic invasion might be useful in determining the optimal adjuvant therapy in the early postoperative stage for distal cholangiocarcinoma.